Progress in Cryptology -- INDOCRYPT 2015 16th International Conference on Cryptology in India, Bangalore, India, December 6-9, 2015, Proceedings - Biryukov, Alex; Goyal, Vipul (Security and Cryptology, 2015)
This book constitutes the refereed proceedings of the 16th International Conference on Cryptology in India, INDOCRYPT 2015, held in Bangalore, India, in December 2015. The 19 revised full papers presented in this book were carefully reviewed and selected from 60 submissions. The papers are organized in topical sections on public key encryption; cryptanalysis; side channel attacks; information theoretic cryptography; and lightweight cryptography.